Do customers use and recommend Islamic credit cards? - Mohammed Usman, Dariyoush Jamshidi, (Opción, 2020)
The study aims to investigate whether customers use and recommend Islamic credit cards or not. Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used to analyze the collected data from respondents. The results indicated that relative advantage, compatibility, observability, and customer awareness have a significant direct effect on the intention to use ICC. In conclusion, the issuer banks are expected that by publishing cogent information regarding ICC which leads to better market of this Islamic service to end-users, increase adoption and usage of ICC.